Advances in targeting estrogen synthesis and receptors in patients with endometriosis. (2nd November 2022) - Clemenza, Sara; Vannuccini, Silvia; Ruotolo, Agostino; Capezzuoli, Tommaso; Petraglia, Felice
ABSTRACT: Introduction: Endometriosis is an estrogen-dependent disease on the background of progesterone resistance. Increased estrogen production, low estrogen metabolization, and altered estrogen receptors (ERs) expression contribute to the hyperestrogenic milieu within endometriotic lesions. Since estrogens play a crucial role in the pathogenesis of the disease, inhibition of estrogen production is one of the main targets of available and emerging drugs. Areas covered: Firstly, we described the molecular alterations responsible for estrogen dependence. Secondly, we reviewed available and emerging treatments that interfere, through central (gonadotropin-releasing hormone analogs (GnRH-a), GnRH antagonists) or local mechanisms (aromatase inhibitors (AIs), inhibitors of steroid sulfatase (STS) and hydroxysteroid dehydrogenase type 1 (17β-HSD1)), with estrogen dependence. Finally, we focused on emerging treatments targeting ERs (selective estrogen receptor modulators (SERMs), estrogen receptors agonists, and antagonists). Expert opinion: Available treatments interfering with estrogen pathways exert a contraceptive effect, have hypoestrogenic side effects, and cannot prevent or definitively treat the disease. Preclinical and animal studies are focusing on emerging drugs targeting ERs in order to overcome limitations of available treatments. These treatments may represent a promising option, as they may produce a more specific inhibition of disease activity within endometriotic implants, avoiding prolonged hypoestrogenic status and limiting systemic side effects.